2015
DOI: 10.1073/pnas.1424194112
|View full text |Cite
|
Sign up to set email alerts
|

Place recognition and heading retrieval are mediated by dissociable cognitive systems in mice

Abstract: A lost navigator must identify its current location and recover its facing direction to restore its bearings. We tested the idea that these two tasks-place recognition and heading retrieval-might be mediated by distinct cognitive systems in mice. Previous work has shown that numerous species, including young children and rodents, use the geometric shape of local space to regain their sense of direction after disorientation, often ignoring nongeometric cues even when they are informative. Notably, these experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 51 publications
(47 reference statements)
7
48
0
Order By: Relevance
“…This evidence suggest that, coherently with its interconnectivity with the hippocampus, the RCS may selectively engaged in translating the stored allocentric reference frame to an egocentric one thanks to a re-establishment of an "ego-oriented bearing" [18], resulting from the continuous synchronization between the inter-object direction in the environment in respect to egocentric current heading. A recent study carried out by Julian and colleagues gave support to our findings [33]. They examined the navigational behavior of mice in two tasks, in which animals had to recognize the chamber in which they were located (i.e., place recognition) and to retrieve their facing direction within that chamber (i.e., heading retrieval).…”
Section: Discussionsupporting
confidence: 70%
“…This evidence suggest that, coherently with its interconnectivity with the hippocampus, the RCS may selectively engaged in translating the stored allocentric reference frame to an egocentric one thanks to a re-establishment of an "ego-oriented bearing" [18], resulting from the continuous synchronization between the inter-object direction in the environment in respect to egocentric current heading. A recent study carried out by Julian and colleagues gave support to our findings [33]. They examined the navigational behavior of mice in two tasks, in which animals had to recognize the chamber in which they were located (i.e., place recognition) and to retrieve their facing direction within that chamber (i.e., heading retrieval).…”
Section: Discussionsupporting
confidence: 70%
“…A visual cue that had been previously shown to be discriminable to both oriented and disoriented mice was present along one wall [6]. To disorient the mouse prior to the start of each trial, the mouse was removed from the chamber and placed in a small, lidded cylinder, which was subjected to four full clockwise and counterclockwise rotations.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, nongeometric cues that could potentially distinguish the geometrically equivalent corners, such as a marking along one wall, are often ignored. This pattern of results—observed across numerous species including birds [5], rodents [4,6], and humans [7]—indicates that reorientation behavior is strongly informed by the spatial geometry of the environment.…”
Section: Introductionmentioning
confidence: 93%
“…For example, recent work in our lab demonstrated a behavioral dissociation between local coordinate and global identity representations when rodent navigators were required to reorient themselves to their surroundings before locating a goal (Julian, Keinath, Muzzio, & Epstein, 2015). Previous studies had established that after disorientation, rodents (Cheng, 1986), humans (Hermer & Spelke, 1994; Learmonth, Newcombe, & Huttenlocher, 2001; Lee & Spelke, 2011), and many other species (Lee, Ferrari, Vallortigara, & Sovrano, 2015; Vallortigara, 2009) exhibit “geometric errors” in their search patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this search pattern is often unaffected by non-geometric cues such as colors or patterns on a wall that could potentially disambiguate these two geometrically equivalent corners. We demonstrated that mice will, however, use these non-geometric cues to determine which chamber they are in—even while simultaneously ignoring them as a guide to locations within the chamber (Julian et al, 2015). That is, the mice used visual features to establish their coarse location within the wider world (e.g.…”
Section: Discussionmentioning
confidence: 99%